2020
DOI: 10.1002/slct.202001008
|View full text |Cite
|
Sign up to set email alerts
|

Minor Biomass Particle Size for an Efficient Cellulose Accessibility and Enzymatic Hydrolysis

Abstract: Sugarcane bagasse is a recalcitrance lignocellulosic material with difficult to structure disorganize and it has low cellulose accessibility, negatively influencing the enzymatic saccharification. This study identified the minor particle size that resulted in the efficient diluted acid pretreatment (10 % m/m, 121°C/ 30 min) of sugarcane bagasse and a more recalcitrant material, that is external fraction (2 to 3 mm from the extremity, containing epidermis). Particle sizes were obtained by sieving sugarcane baga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Fernandes et al. found an increase in glucose yield during enzymatic hydrolysis of sugarcane bagasse of 76 % with particles smaller than 60 mesh compared to native particle size 25. However, the achieved glucose yield of milled biomass particles is still unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernandes et al. found an increase in glucose yield during enzymatic hydrolysis of sugarcane bagasse of 76 % with particles smaller than 60 mesh compared to native particle size 25. However, the achieved glucose yield of milled biomass particles is still unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated a preferential hydrolysis of smaller particles by cellulases as well as a higher saccharification rate of substrates with a smaller particle size [24]. Fernandes et al found an increase in glucose yield during enzymatic hydrolysis of sugarcane bagasse of 76 % with particles smaller than 60 mesh compared to native particle size [25]. However, the achieved glucose yield of milled biomass particles is still unsatisfactory.…”
Section: Biocatalysis Of Biomasses With Different Lignin Contentsmentioning
confidence: 99%
“…Sugarcane bagasse was donated by the CTC (Centro de Tecnologia Canavieira -Piracicaba -SP, Brazil), was successively washed with distilled water aiming to remove reserve sugar residues, and then was oven-dried at 55 °C for 48 h. After that, biomass was ground in 20-mesh a knife mill (825 μm) [24]. The biomass was conditioned in plastic bags and stocked.…”
Section: Methodsmentioning
confidence: 99%
“…Curaua has a small lignin content and this factor can facilitate the access of chemical reagents to hemicellulose. Sugarcane bagasse fibers, for example, have 43.36% cellulose, 23.27% hemicellulose, and 21.38% lignin [ 10 ]. Despite having a higher percentage of hemicellulose compared to curaua fibers, the comparatively high percentage of lignin makes the hemicellulose extraction process difficult.…”
Section: Introductionmentioning
confidence: 99%